(untitled) (Acta Polytechnica CTU Proceedings, 2014)
X-ray polarimetry promises to give qualitatively new information bout high-energy astrophysical sources, such as binary black hole systems, micro-quasars, active galactic nuclei, and gamma-ray bursts. We designed, built and tested ahard X-ray polarimeter, X-Calibur, to be used in the focal plane of the InFOCuS grazing incidence hard X-ray telescope.X-Calibur combines a low-Z Compton scatterer with a CZT detector assembly to measure the polarization of 20−60 keV X-rays making use of the fact that polarized photons Compton scatter preferentially perpendicular to the electric field orientation; in principal, a similar space-borne experiment could be operated in the 5−100 keV regime. X-Calibur achieves a high detection efficiency of order unity.